BEHAVIOR OF ACCESSING ARTIFICIAL INTELLIGENCE (AI) CONTENT IN INDONESIA: DESCRIPTIVE ANALYSIS BASED ON APJII 2025 SECONDARY DATA - Meykel Djuuna; Fricy Rumintjap; Benhard Lanto (JURNAL ILMIAH EDUNOMIKA, 2026)
This study aims to describe Indonesian internet users' behavior in accessing Artificial Intelligence (AI) content, using secondary data from the 2025 Indonesian Internet Profile Survey conducted by the Indonesian Internet Service Providers Association (APJII). The research adopts a descriptive design, without hypothesis testing or inferential statistics. Data are taken as reported by APJII in the form of percentages and charts, then interpreted through descriptive–narrative analysis. The results indicate a clear gap between high national internet penetration and relatively low AI adoption; only a minority of respondents report using AI, while the majority have not yet engaged with it. Among AI users, educational purposes represent the most common use, followed by entertainment, whereas virtual assistant and productivity functions remain limited. For non-users, the main reasons are not knowing what AI is, not knowing how to use it, and perceiving no need for AI. AI usage is also concentrated among younger generations, particularly Generation Z. The novelty of this study lies in constructing a national descriptive map of AI content access behavior based on APJII’s 2025 AI module, and interpreting it within the framework of digital consumer behavior and AI literacy.